2018
DOI: 10.3389/fnins.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Protects Dopaminergic Neurons From Dopamine-Induced Neurodegeneration via Synergistic Adenosine-Dopamine D2-Like Receptor Interactions in Transgenic Caenorhabditis elegans

Abstract: Previous studies have suggested that caffeine reduces the risk of L-DOPA-induced dyskinesia. However, caffeine is also known to promote dopamine signaling, which seemingly contradicts this observed effect. To this end, the study aimed to clarify the mechanism of caffeine neuroprotection in vivo when excess dopamine is present. Transgenic Caenorhabditis elegans (UA57) overproducing dopamine was exposed to caffeine for 7 days and monitored by observing GFP-tagged dopaminergic (DA) neurons via fluorescence micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…This finding is independent of the neuronal profile, noting that nematodes exposed to 60LC20 had significant neurodegeneration compared with those exposed to 60LC10 (p < 0.05), yet the body-bending rates of both treatment groups were significantly less than that of caffeine or L-DOPA alone. Although these rates were significantly greater than in vehicle, these findings suggest that caffeine greatly reduces the rate of locomotion when coadministered with L-DOPA, which may point out to its effect on presynaptic autoreceptor dopamine D2-like receptors (DOP2Rs) that are inhibitory when dopamine release is in excess (Manalo and Medina 2018a).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…This finding is independent of the neuronal profile, noting that nematodes exposed to 60LC20 had significant neurodegeneration compared with those exposed to 60LC10 (p < 0.05), yet the body-bending rates of both treatment groups were significantly less than that of caffeine or L-DOPA alone. Although these rates were significantly greater than in vehicle, these findings suggest that caffeine greatly reduces the rate of locomotion when coadministered with L-DOPA, which may point out to its effect on presynaptic autoreceptor dopamine D2-like receptors (DOP2Rs) that are inhibitory when dopamine release is in excess (Manalo and Medina 2018a).…”
Section: Resultsmentioning
confidence: 88%
“…Previously, we have shown that C. elegans strain UA57 exposed to 10 mM caffeine had less degeneration of the four cephalic and two anterior deirid neurons, which otherwise would have degenerated drastically in vehicle (0.1% DMSO). Further, we elucidated and proposed a mechanism thought to be conserved between C. elegans and mammals, that is, the close communication between adenosine receptor antagonism and activation of dopamine D2like receptors (DOP2Rs) in modulating excessive dopamine synthesis or release (Manalo and Medina 2018a). However, there is no clear-cut correlation between the neuroprotection conferred by caffeine and its effects on behaviour, which is probably more relevant to drug discovery and development for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations